Respuesta :

The primitive function for [tex]f(x) = 4e^{2x} + e^{-x}[/tex] is given by it's indefinite integral.

To calculate it, recall:

[tex]\frac{d}{dx}e^{ax}=ae^{ax}[/tex]

[tex]\int c f(x)dx = c\int f(x)dx[/tex]

Let's begin

[tex]\int 4e^{2x}+e^{-x}dx \\4\int e^{2x}dx+ \int e^{-x}dx\\4\frac{e^{2x}}{2}+\frac{e^{-x}}{-1} + c\\[/tex]

[tex]F(x) = 2e^{2x}-e^{-x} +c[/tex]

To find the costant, we just need to use the fact that [tex]F(0)=2[/tex]

[tex]F(0) = 2 \\4e^{0}+e^{0} + c =2\\5+c =2\\c=-3[/tex]

Therefore,

[tex]\boxed{F(x) = 2e^{2x} - e^{-x} -3 }[/tex]

ACCESS MORE